Optimization Of Cultural Conditions For Cellulase-Free Xylanase Production By Mutant Strain Of Alkalophilic Cellulosimicrobium Sp. Ckmx1 In Submerged Fermentation (Applied Biological Research, 2013)
This paper reports optimization of cultural conditions for xylanase production  bymutantstrains of Cellulosimicrobiumsp. CKMX1 in submerged fermentation. Alkalophilic Cellulosimicrobium sp. CKMX1, capable of producing xylanase,  was isolated from mushroom compost. Xylanase production by this strain was  enhanced by ethyl methanesulfonate (5-70 mg mL-1) mutation and by optimizing  the process parameters in submerged fermentation. Mutant strain E5 with  hyper xylanase production was obtained after treating wild strain with ethyl  methanesulfonate on the basis of xylanase activity index and xylanase activity  in liquid medium. Cultural conditions were optimized for parent and mutant  strain and incubation period of 72 h, incubation temperature of 35+1⁰ C, pH of 8.0; 1% inoculum size: and xylan as carbon source yielded high xylanase.  Mutant E5 was 22.99% more efficient than parent strain. Results indicated the  potential of alkalophilic Cellulosimicrobium sp. CKMX1 and its hyper xylanase  producing mutant strain E5 to be promising for pulp and paper industry.
Keywords: Alkalophilic bacterium; Cellulosimicrobium; mushroom compost; mutation; xylanase